Young Saudi consumers and corporate social responsibility: an Islamic "CSR tree" model. Issue 12 (7th August 2018) - Alfakhri, Yazeed; Nurunnabi, Mohammad; Alfakhri, Demah
Abstract : Purpose: In response to the scarcity of research on Islamic corporate social responsibility (CSR), the purpose of this paper is to explore how young Saudi consumers perceive CSR from an Islamic perspective. The study is focused on Saudi Arabia, a Muslim country, and the largest exporter of petroleum in the world. Design/methodology/approach: The present study uses a qualitative methodology with 34 in-depth interviews undertaken in two major Saudi cities (Tabouk and Riyadh). Findings: Utilising social contract theory, this study contributes to the literature by developing an Islamic "CSR Tree" model (which consists of three parts: "roots", "trunk", and "crown") to increase the understanding of Islamic CSR (i-CSR) and consumer behaviour. The roots are hidden, while the trunk and crown are visible. In particular, private social responsibility (the roots of the CSR Tree) incorporating Sadaqa, or values and intention, is the fundamental component on which organisations should base their CSR strategy from an Islamic perspective. The study also reveals that internal, external, and private social responsibilities are connected, and all are dependent on each other. The higher the level of private social responsibility exhibited, the higher the level of external social responsibility. Originality/value: According to the CSR Tree model presented in this study, an organisation should avoid Riya (showing off) as this would represent shirk or idolatry, which is the opposite of Tawhid . The findings are particularly relevant for advancing the concept of i-CSR and for considering complex perspectives less travelled in the CSR literature. The study suggests that the best strategy for an organisation wishing to pursue an i-CSR agenda would be to balance internal and external responsibilities, and to bear in mind that private responsibility should be the motivation for action, and that CSR should be applied for the benefit of society.